Essential oils affect populations of some rumen bacteria in vitro as revealed by microarray (RumenBactArray) analysis - Patra, Amlan K.; Yu, Zhongtang (Frontiers in Microbiology, 2015)
In a previous study origanum oil (ORO), garlic oil (GAO), and peppermint oil (PEO) were shown to effectively lower methane production, decrease abundance of methanogens, and change abundances of several bacterial populations important to feed digestion in vitro. In this study, the impact of these essential oils (EOs, at 0.50 g/L), on the rumen bacterial community composition and population was further examined using the recently developed RumenBactArray. Species richness (expressed as number of operational taxonomic units, OTUs) in the phylum Firmicutes, especially those in the class Clostridia, was decreased by ORO and GAO, but increased by PEO, while that in the phylum Bacteroidetes was increased by ORO and PEO. Species richness in the genus Butyrivibrio was lowered by all the EOs. Increases of Bacteroidetes OTUs mainly resulted from increases of Prevotella OTUs. Overall, 67 individual OTUs showed significant differences (P≤0.05) in relative abundance across the EO treatments. The predominant OTUs affected by EOs were diverse, including those related to Syntrophococcus sucromutans, Succiniclasticum ruminis, and Lachnobacterium bovis, and those classified to Prevotella, Clostridium, Roseburia, Pseudobutyrivibrio, Lachnospiraceae, Ruminococcaceae, Prevotellaceae, Bacteroidales, and Clostridiales. In total, 60 OTUs were found significantly (P≤0.05) correlated with feed degradability, ammonia concentration, and molar percentage of volatile fatty acids. Taken together, this study demonstrated extensive impact of EOs on rumen bacterial communities in an EO type-dependent manner, especially those in the predominant families Prevotellaceae, Lachnospiraceae and Ruminococcaceae. The information from this study may aid in understanding the effect of EOs on feed digestion and fermentation by rumen bacteria.